A Pilot Study of the Maximum Interincisal Distance among Adult Northern and Southern Nigerians - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Objective:To study the average maximum interincisal distance (MID) and its association with individual physical parameters and dietary pattern in a representative convenient sample of healthy adult Nigerians from two ethnic groups.Materials and Methods:This was a pilot cross-sectional study of healthy adults, free of temporomandibular joint (TMJ) disorders, aged 18–58 years in Ile-Ife (Southwest Nigeria) and Kano (Northwest Nigeria). MID, body weight, and height were determined using a clean wooden spatula on a transparent plastic linear gauge, calibrated body weight electronic scale, and wall-mounted height scale, respectively. Dietary habits and history were assessed using a validated structured questionnaire. MID was compared in each group and related to subjects’ age, sex, height, and weight.Results:Of 853 subjects screened, 794 (93.1%), aged 18–58 years, met the inclusion criteria. About 393 (49.5%) and 401 (50.5%) subjects were from the Northwest (Kano City) and Southwest (Ile-Ife), respectively. The mean age of the subjects from the Northwest and Southwest Nigeria was 35.4 years and 26.7 years, respectively, and M:F ratio was 1:1.02. Female subjects recorded higher body mass index (BMI) and were slightly older than the males. Mean MID (SD) values in millimeters were 45.68 (6.7), 47.60 (7.73), and 46.69 (7.29) in the Southwest, Northwest, and combined groups, respectively. MID was significantly higher in males than females, peaked at age 33 years in both the sexes and, thereafter, decreased with increasing age.Conclusion:The MID vary with ethnic origin, weight, height, age, and BMI. A peak MID in adult appears to exist at about 33 years.